Filing Agents and Information Leakage - Bargeron, Leonce; Clifford, Christopher P.; Qiu, Tian (Journal of Financial and Quantitative Analysis, 2025)
Abstract Filing agents—intermediaries used by 80% of U.S. firms—are associated with leakage of information that affects stock prices. Prior to the public release of a securities filing, most firms outsource the final processing and submission of the filing to a third-party filing agent. We find leakage is higher when firms use filing agents than when firms self-file, particularly pre-2018. Leakage is greater when the private information is more valuable and decreases when firms switch to self-filing. Our research suggests filing agents, and a firm’s choice to use them, are an important, understudied channel for the leakage of private information.